Theoretical Foundations of Human Capital Education in Economic Growth and Development Management - Piontek, Franciszek; Piontek, Barbara (Problemy Ekorozwoju, 2019)
In this paper we try to answer the following questions: How will the nature of science change? And How will the education of human capital change and what will it be like, as a result of changing the nature of science, in structural and functional terms and what consequences for the management of growth and development will it have? Change in the nature of science consists of negating the basic axiom, which is the principle of contradiction YES is not NO replacing it with paradigm of deregulation YES=NO=MAYBE. Modify in quality of the education of human capital, the restriction of general education; the limitation of competencies resulting from general education may have adverse effects in the demanding technology market and may eliminate advantages in the processes of automation and robotization. The most important conclusions from the discussion are that science and education are strategic categories and determine the quality of human capital and the nature of science and education in the strategic dimension cannot be determined solely by neither short-term market needs, nor by research teams that are narrowly specialized and guided by their own determinants and priorities, education in the strategic dimension cannot be managed according to the rules of crisis management, ad hoc and for market needs.